An ultra-short-period transiting super-Earth orbiting the M3 dwarf TOI-1685 - Bluhm, Paz; Pallé, E.; Molaverdikhani, Karan; Kemmer, Jonas; Hatzes, A. P.; Kossakowski, Diana; Stock, Stephan; Caballero, J. A.; Lillo-Box, J.; Béjar, V. J. S.; Soto, M. G.; Amado, P. J.; et al. (Astronomy and astrophysics, 2021)
Dynamical histories of planetary systems, as well as the atmospheric evolution of highly irradiated planets, can be studied by characterizing the ultra-short-period planet population, which the TESS mission is particularly well suited to discover. Here, we report on the follow-up of a transit signal detected in the TESS sector 19 photometric time series of the M3.0 V star TOI-1685 (2MASS J04342248+4302148). We confirm the planetary nature of the transit signal, which has a period of Pb = d, using precise radial velocity measurements taken with the CARMENES spectrograph. From the joint photometry and radial velocity analysis, we estimate the following parameters for TOI-1685 b: a mass of Mb = M⊕, a radius of Rb = R⊕, which together result in a bulk density of ρb = g cm−3, and an equilibrium temperature of Teq = K. TOI-1685 b is the least dense ultra-short-period planet around an M dwarf known to date. TOI-1685 b is also one of the hottest transiting super-Earth planets with accurate dynamical mass measurements, which makes it a particularly attractive target for thermal emission spectroscopy. Additionally, we report with moderate evidence an additional non-transiting planet candidate in the system, TOI-1685 [c], which has an orbital period of Pc = d.